Potensi Pantai Panrangluhung di Bira Kabupaten Bulukumba sebagai Destinasi Wisata - Musawantoro, Muhammad; Ridwan, Masri (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2019)
This study aims to identify the characteristics of tourism in Panrangluhung Beach, Bira Village, Bontobahari District, Bulukumba Regency, South Sulawesi Province, Indonesia. Data collection techniques by survey, documentation and observation. This study employs spatial analysis and snowball sampling to analyze and collect data on the distribution of accommodation, attractions and tourist attractions at the study site. As for data visualization, geographic information system analysis is then performed with the existing data overlay method. The results show that the Panrangluhung beach area as a typology of marine tourism attraction with a coastline of 1,650 meters and cultural tourism at the center of phinisi shipbuilding. Recommendations from this study are to revitalize the 45-meter long coastal area in the southern part of the study site, including: the installation of a sign system and directing beach cleanliness.